Cerebellar transcranial alternating current stimulation modulates human gait rhythm. (July 2020) - Koganemaru, Satoko; Mikami, Yusuke; Matsuhashi, Masao; Truong, Dennis Q.; Bikson, Marom; Kansaku, Kenji; Mima, Tatsuya
Highlights: tACS was given on left cerebellum during over-ground walking in healthy subjects. The frequency of tACS were set close to that of their gait cycle. It significantly entrained their gait rhythm. The entrainment phase was inverted with the inverted direction of the tACS currents. It suggests that tACS modulates rhythm generation system in cerebellum. Abstract: Although specific brain regions are important for regularly patterned limb movements, the rhythm generation system that governs bipedal locomotion in humans is not thoroughly understood. We investigated whether rhythmic transcranial brain stimulation over the cerebellum could alter walking rhythm. Fourteen healthy subjects performed over-ground walking for 10 min during which they were given, in a random order, transcranial alternating current stimulation (tACS) over the left cerebellum at the approximated frequency of their gait cycle, tACS over the skin of the scalp, and during sham stimulation. Cerebellar tACS showed a significant entrainment of gait rhythm compared with the control conditions. When the direction of the tACS currents was symmetrically inverted, some subjects showed entrainment at an approximately 180° inverted phase, suggesting that gait modulation is dependent on current orientation. These findings indicate that tACS over cerebellum can modulate gait generation system in cerebellum and become an innovative approach for the recovery of locomotion in patients with gait disturbances caused by CNS disorders.